The ADCYAP1R1 Gene Is Correlated With Posttraumatic Stress Disorder Symptoms Through Diverse Epistases in a Traumatized Chinese Population - Wang, Li; Zhang, Jingyi; Li, Gen; Cao, Chengqi; Fang, Ruojiao; Liu, Ping; Luo, Shu; Zhao, Guangyi; Zhang, Yingqian; Zhang, Kunlin (Frontiers in Psychiatry, 2021)
The ADCYAP1R1 (Adenylate Cyclase Activating Polypeptide 1 (Pituitary) Receptor) gene is associated with the hypothalamic-pituitary-adrenal (HPA)axis, which controls stress responses. The single nucleotide polymorphism (SNP) ofADCYAP1R1, rs2267735, has been investigated in many studies to test its association with posttraumatic stress disorder (PTSD), but the results have not been consistent. It is worth systematically exploring the role of rs2267735 in PTSD development. In this study, we analyzed rs2267735 in 1132 trauma-exposed Chinese individuals (772 females and 360 males). We utilized the PTSD Checklist for DSM-5 (PCL-5) to measure PTSD symptoms. Then, we analyzed the main, G×E (rs2267735×trauma exposure) and G×G (with other HPA axis gene polymorphisms) effects of rs2267735 on PTSD severity (total symptoms). There were no significant main or G×E effects (P> 0.05). The G×G ADCYAP1R1-FKBP5 interaction (rs2267735×rs1360780) was associated with PTSD severity (beta = -1.31 and P = 0.049) based on all subjects, and the G×G ADCYAP1R1-CRHR1 interaction (rs2267735×rs242924) was correlated with PTSD severity in men (beta = -4.72 and P = 0.023). Our study indicated that the ADCYAP1R1 polymorphism rs2267735 may affect PTSD development through diverse gene-gene interactions.